SEMANTIC REPRESENTATION OF INCONSISTENT INTUITIONISTIC THEORIES - Shramko, Y. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2017)
In this paper I propose a new method of semantic modeling for intuitionistic logic and provide an intuitive justification to this method. I put in the focus of consideration a concept of intuitionistic theory which is the basic concept of the whole analysis.